An overview of the VISTA trial: Newly diagnosed, untreated patients with multiple myeloma ineligible for stem cell transplantation - Spicka, I.; Mateos, M.V.; Redman, K.; Dimopoulos, M.A.; Richardson, P.G. (Immunotherapy, 2011)
Multiple myeloma, a plasma cell neoplasm, is the second most common hematologic malignancy after non-Hodgkins lymphoma and is responsible for 2% of cancer deaths. Melphalan and prednisone (MP) has been the standard treatment in elderly patients for many decades. The VISTA study evaluated the effect of this combination with or without the first-in-class proteasome inhibitor bortezomib in newly diagnosed myeloma patients who were not candidates for autologous stem cell transplantation. Altogether 682 patients were enrolled and prospectively randomized in this trial. All patients received nine 6-week cycles of oral melphalan (9 mg/m 2) and prednisone (60 mg/m 2) on days 1-4, either alone or with bortezomib administered intravenously (1.3 mg/m 2 on days 1, 4, 8, 11, 22, 25, 29 and 32 during the first four cycles and on days 1, 8, 22, 29 during remaining course of therapy). Median time to progression (the primary end point of the trial) was 24 months in the bortezomib-containing group compared with 16.6 months in the control group (p < 0.001). Response was evaluated in 337 patients receiving bortezomib compared with 331 patients in the control group who received MP alone; the percentages of partial response or better was 71 vs 35% (p < 0.001), with complete response seen in 30 vs 4%, respectively (p < 0.001). Median response duration in both groups was 19.9 versus 13.1 months, respectively. Median overall survival has not been reached in VMP group compared with 43 months in the MP group (p < 0.001), and this benefit is maintained after long term follow-up and subsequent antimyeloma therapies. Hematological adverse events (AEs) were similar in both groups, although patients in the bortezomib group experienced more frequent peripheral sensory neuropathy (including 13% grade 3, with less than 1% grade 4). Overall, the occurrence of grade 3 AEs was higher in patients receiving bortezomib (53 vs 44%, p = 0.02), but the risk of grade 4 AEs was identical (28 vs 27%). These results confirm the superiority of MP plus bortezomib combination over MP therapy in treatment-naive patients with newly diagnosed multiple myeloma who are ineligible for autologous stem cell transplantation. © 2011 Future Medicine Ltd.
Keywords: bortezomib; multiple myeloma; peripheral neuropathy; proteasome inhibition; treatment-naive older patients